Three Years of Stable Water Isotope Data of Daily Rain Samples Collected from Three Geomorphic Regions of India - Sundara Pandian Rajaveni; S. S. Nimya; Saikat Sengupta; Amey Datye; Dipankar Sarma (Scientific Data)
Abstract High-frequency precipitation (solid/liquid) isotope datasets are useful for identification of moisture sources and various dynamical and thermodynamical processes controlling precipitation formation. Here, we report three-year (2019–2021) daily rain isotope (both oxygen, δ18O hereafter, and hydrogen, δ2H, hereafter) datasets from three unique locations in India during the Indian Summer Monsoon (ISM). The locations are- (1) Port Blair- an island situated in the Bay of Bengal (BoB); (2) Mahabaleshwar, located at the crest of the Western Ghats Mountain; and (3) Tezpur, in northeast India, situated close to a dense forest. These stations receive moisture from different sources and experience different rain mechanisms during ISM. Therefore, the isotope datasets presented here would be useful for envisaging the impact of diverse rain formation processes on isotope values during the ISM.